A New Member of the Graphene Family: Graphene Acid - Jankovský, Ondřej; Nováček, Michal; Luxa, Jan; Sedmidubský, David; Fila, Vlastimil; Pumera, Martin; Sofer, Zdeněk (Chemistry (Weinheim an der Bergstrasse, Germany), 2016)
A new member of the family of graphene derivatives, namely, graphene acid with a composition close to C1 (COOH)1 , was prepared by oxidation of graphene oxide. The synthetic procedure is based on repeated oxidation of graphite with potassium permanganate in an acidic environment. The oxidation process was studied in detail after each step. The multiple oxidations led to oxidative removal of other oxygen functional groups formed in the first oxidation step. Detailed chemical analysis showed only a minor amount of other oxygen-containing functional groups such as hydroxyl and the dominant presence of carboxyl groups in a concentration of about 30 wt %. Further oxidation led to complete decomposition of graphene acid. The obtained material exhibits unique sorption capacity towards metal ions and carbon dioxide. The highly hydrophilic nature of graphene acid allowed the assembly of ultrathin free-standing membranes with high transparency.
Keywords: graphene derivatives; oxidation; graphene; carboxylic acids; membranes